PERAN IBU RUMAH TANGGA DALAM MENDUKUNG EKONOMI KELUARGA MISKIN - Wardani, Erfiani S; ., Suparno (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2016)
TheÂ Â titleÂ Â ofÂ Â theÂ Â researchÂ Â isÂ Â â€œPERANÂ Â Â IBUÂ Â RUMAHÂ Â TANGGAÂ Â Â DALAM MENDUKUNG Â EKONOMI Â KELUARGA Â MISKIN Â (source Â of Â the Â data Â :Â Mojo Â district, Gubeng- Surabaya)â€ the purpose of the research is to know about the effect of education, time of work, and experience Â of housewives Â concern with income and also to understand about main variable of housewivesâ€™ income in Mojo district. Kinds of the data and data sources are used qualitative approach with the primery data is interview with the society of Mojo district. Subjects to change of the thesis are dependent variable Â is Â income Â (Y), Â Independent Â variable Â isÂ education Â (X1), Â Time Â work Â (X2), Â and experience (X3). The tools of the analysis is doubled regression linear method, test â€˜tâ€™, test â€˜fâ€™, coefficient determination. The result of the thesis be based on the research such as: Y=0.499 + 0.268 X1 + 0.295 X2 + 0.216 X3 + e. The writer also gained score of â€˜thitungâ€™ about education 2.509, time work 2. 357 and the experience 2.227 with â€˜ttableâ€™ 2.009. Meanwhile, simultaneousâ€™ test is â€˜Fhitung 6.614 > Ftable 2.81. The result is Â H0 was denied and Ha was accepted. Conclusion Â ofÂ the Â research Â is showed Â that Â eachÂ ofÂ independent Â variable Â againt Â the dependentÂ variable are have the positive value, but according to simultaneousâ€™ Â test is low effect, Â with Â the Â assumption Â have Â other Â variables Â outer Â part Â ofÂ the Â research Â which Â can influence and be related to independent and dependent variables.Keywords : Income, education, time work, and experince.